Accelerated oxidation during air flooding in a low temperature reservoir. (2nd January 2017) - Li, Xinghong; Liu, Jing; Pu, Jingyang; Pu, Chunsheng; Li, Qi; Gu, Xiaoyu
ABSTRACT: To ensure the safety of application of air flooding in a low temperature reservoir, the accelerated oxidization of oxygen and the crude oil is studied at low temperature. The stabilized chlorine dioxide solution can be used as a type of catalyst, which can accelerate the reaction rate of oxygen and the crude oil to decrease the concentration of remaining oxygen when the gas reaches the production well. The experimental results of oxidization show that O2 concentration is greatly reduced and CO2 concentration is greatly increased on condition with catalyst. In addition, the amount of heavy components can be further reduced and the amount of light components can be further increased. These can ensure the safety of application of air flooding in low temperature reservoir. The experimental results of adaptability of the accelerated oxidation under different water saturation show air flooding can be better used in the low-temperature reservoir with low water saturation on condition with catalyst but cannot be used in the low-temperature reservoir with high water saturation. The experimental results can provide theoretical basis for the application of air flooding in a low-temperature reservoir.